2011
DOI: 10.4000/syria.914
|View full text |Cite
|
Sign up to set email alerts
|

Qarassa, un site du Bronze ancien et moyen en Syrie du Sud

Abstract: -À la suite d'une prospection régionale du plateau basaltique du Leja, le site de Qarassa a été choisi pour la fouille en raison de sa représentativité chronologique du Natoufien à l'âge du Fer qui en fait la première référence chronostratigraphique longue pour la zone basaltique. Le tell sud de Qarassa est occupé du milieu du IV e jusqu'au deuxième quart du I er millénaire. On propose ici une synthèse des résultats de la fouille des niveaux du Bronze ancien de cette agglomération fortifiée.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…To achieve this, a more precise chronological framework must be established. Considering that Levantine megalithic monuments have been attributed to the 4th and 3rd millennia BCE, thanks in part to excavations over the last 30 years (Braemer et al, 2004(Braemer et al, , 2011Fernandez-Tresguerres Velasco et Junceda Quintana, 1991;Kerner, 2019;Polcaro et Muniz, 2018;Steimer-Herbet, 2006), the MEG-A project aims to increase the dating of these monuments through the application of various methods. Luminescence dating 5 is thus being employed within this ongoing research in Menjez, as it has already demonstrated its potential for dating megaliths, notably at Rujm el-Hiri (Freikman et Porat, 2017).…”
Section: Corpusmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this, a more precise chronological framework must be established. Considering that Levantine megalithic monuments have been attributed to the 4th and 3rd millennia BCE, thanks in part to excavations over the last 30 years (Braemer et al, 2004(Braemer et al, , 2011Fernandez-Tresguerres Velasco et Junceda Quintana, 1991;Kerner, 2019;Polcaro et Muniz, 2018;Steimer-Herbet, 2006), the MEG-A project aims to increase the dating of these monuments through the application of various methods. Luminescence dating 5 is thus being employed within this ongoing research in Menjez, as it has already demonstrated its potential for dating megaliths, notably at Rujm el-Hiri (Freikman et Porat, 2017).…”
Section: Corpusmentioning
confidence: 99%
“…Several thousand megalithic monuments have been documented in the area; however, only 300 of them have been excavated. Digs have been carried out in Israel (Aveni & Mizrachi, 1998;Bahat, 1972;Epstein, 1985;Freikman & Porat, 2017;Vinitzky, 1992), Jordan (Fernandez-Tresguerres Velasco & Junceda Quintana, 1991;Fernandez-Tresguerres Velasco, 2011;Kerner, 2019;Kerner et al, 2017;Polcaro et al, 2014;Polcaro & Muniz, 2018;Kołodziejczyk, personal communication), Syria (Braemer et al, 2004(Braemer et al, , 2011Steimer-Herbet, 2006;Steimer-Herbet & Besse, 2017), and Lebanon (Steimer-Herbet et al, 2022;Tallon, 1964). Some researchers have also undertaken a review of the constantly evolving research on this subject (Avner, 2002;Fraser, 2018;Steimer-Herbet, 2004-2005.…”
Section: Introductionmentioning
confidence: 99%
“…The archaeological site of Tell Qarassa, located in modern-day Syria (Fig. 1a), is prominently known for its evidence of human occupation since the Epipaleolithic period to the Iron Age [56][57][58] . Located on the shores of an ancient dried up lake, it is described to consist of multiple sites or socalled 'Tells', one of which (Northern Tell) contains remains from Pre-Pottery Neolithic B to Late Chalcolithic settlements, while the other (Southern Tell) holds evidence of Early Bronze to Iron Age remains.…”
Section: Archaeological Contextmentioning
confidence: 99%